The Coke machine : the dirty truth behind the world's favorite soft drink - Blanding, Michael (New York : Avery, 2010)
An expose on the rise of Coca-Cola to become one of the world's most profitable and recognized brands shares unsettling reports on franchise deals in adversarial nations, the role of company products in obesity rates, and the environmental impact of its bottling practices
A brief history of Coke -- Building the brand -- Biggering and biggering -- The battle for schools -- The bottled water lie --'!Toma lo bueno!' --'Syrup in the veins' -- The full force of the law -- All the water in India -- The case against'killer Coke.'
Keywords: Coca-Cola Company -- History; Soft drink industry; Bottled water industry; International business enterprises